2020
DOI: 10.1038/s41586-019-1919-3
|View full text |Cite
|
Sign up to set email alerts
|

Fast two-qubit logic with holes in germanium

Abstract: The promise of quantum computation with quantum dots has stimulated widespread research. Still, a platform that can combine excellent control with fast and high-fidelity operation is absent. Here, we show single and two-qubit operations based on holes in germanium. A high degree of control over the tunnel coupling and detuning is obtained by exploiting quantum wells with very low disorder and by working in a virtual gate space. Spin-orbit coupling obviates the need for microscopic elements and enables rapid qu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
283
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 275 publications
(301 citation statements)
references
References 51 publications
5
283
1
Order By: Relevance
“…Among them, Ge is attracting more and more attention due to its high hole mobility, [ 10–13 ] low effective mass in 2D hole gases, [ 14,15 ] good contacts with metals, [ 16–18 ] strong spin–orbit interactions, [ 19–22 ] capability of isotopic purification, [ 23 ] and compatibility with Si. These attractive features make Ge a promising candidate not only as a transistor channel material but also as a host for spin [ 6,24,25 ] and even topological qubits. [ 26,27 ] Excitingly, the first hole spin qubit [ 6 ] and proximity‐induced superconductivity with a hard gap [ 28 ] have been realized recently in 1D Ge.…”
Section: Figurementioning
confidence: 99%
“…Among them, Ge is attracting more and more attention due to its high hole mobility, [ 10–13 ] low effective mass in 2D hole gases, [ 14,15 ] good contacts with metals, [ 16–18 ] strong spin–orbit interactions, [ 19–22 ] capability of isotopic purification, [ 23 ] and compatibility with Si. These attractive features make Ge a promising candidate not only as a transistor channel material but also as a host for spin [ 6,24,25 ] and even topological qubits. [ 26,27 ] Excitingly, the first hole spin qubit [ 6 ] and proximity‐induced superconductivity with a hard gap [ 28 ] have been realized recently in 1D Ge.…”
Section: Figurementioning
confidence: 99%
“…Early research demonstrated the feasibility of using the SOC for allelectric driving 17,18 , but these experiments were limited by nuclear spins and the coherent driving of a single-hole spin remained an open challenge. More recently, hole spins in group-IV materials have gained attention as a platform for quantum information processing [19][20][21][22] . In particular, hole states in germanium can provide a high degree of quantum dot tunability [23][24][25] , fast and all-electrical driving 20,21 and Ohmic contacts to superconductors for hybrids 26,27 .…”
mentioning
confidence: 99%
“…More recently, hole spins in group-IV materials have gained attention as a platform for quantum information processing [19][20][21][22] . In particular, hole states in germanium can provide a high degree of quantum dot tunability [23][24][25] , fast and all-electrical driving 20,21 and Ohmic contacts to superconductors for hybrids 26,27 . These experiments culminated in the recent demonstration of full two-qubit logic 21 .…”
mentioning
confidence: 99%
“…The exchange interaction is set by the tunnel coupling and detuning, and gaining precise control over these parameters enables to define and operate qubits at their optimal points [5][6][7][8]. Excellent control has already been reported in GaAs [5,6,9], strained silicon [10,11], and more recently in strained germanium [12,13]. Reaching this level of control in silicon metal-oxide-semiconductor (SiMOS) quantum dots is highly desired as this platform has a high potential for complete integration with classical manufacturing technology [14][15][16].…”
mentioning
confidence: 99%